Make A Match Learning Model for High School Students': A Study of Students' Ability to Write Procedure Texts - Yustiawati, Tia; Iskandar; Fatmasari, Eli (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study's objective is to determine the students’ improvement in writing skills using the make-a-match learning model. This type of research is classroom action research, with the 29 students of Grade XII SMAS Al Ittihad Cianjur as research subjects. The research design consists of planning, implementation, observation, and reflection. We used an observation instrument and a test instrument for data collection. The study's findings indicate that students' interests and activities increased during the observation period, rising from 37% in the first cycle to 69.95% in the second. The average value of the previous students' test results increased from 62.72 in the first cycle to 71.12 in the second cycle. Based on the comparison of the average values obtained, there has been an increase in students learning abilities after taking action with the Make a Match learning model. This description suggests that the use of the make-a-match learning model can enhance the ability to learn English.